STRATEGI PEMASARAN KSUS. ”KARYA BAROKAH ” UNTUK MENARIK NASABAH BARU DALAM ERA DIGITAL DI WONOGIRI - Bayu Pramudiyanto; Sumadi; Tho’in, Muhammad (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to analyze the digital marketing strategies implemented by KSUS Karya Barokah, a sharia-based savings and loan cooperative, in its efforts to attract new members in the digital era. Digital transformation is an urgent need for cooperatives to remain competitive against modern financial institutions such as fintech. Using a qualitative approach and case study method, the research was conducted in Wonogiri, Central Java. Data collection techniques include in-depth interviews, direct observation, and document analysis. Findings indicate that the cooperative’s digital strategy remains limited to social media platforms (Facebook, Instagram, WhatsApp Business) and lacks professional integration. Major challenges include limited human resources, low digital literacy among the community, and insufficient marketing budget. Nevertheless, an increase in new members since 2022 shows the positive potential of cooperative digital marketing. The study recommends strengthening cooperative human resource digital capacity, collaborating with local influencers, and developing an integrated sharia-based mobile application. These findings contribute to theoretical discourse on cooperative marketing strategies and provide practical implications for institutional transformation in the digital era.